A case report on attempted suicide by hanging of an adolescent girl - Shakya, Kashyap Narsingh; Bhatta, Anwesh; Bhandari, Bikash (Journal of Kathmandu Medical College, 2018)
Suicidal attempt by hanging is a growing problem during adolescence. Globally, 8.5 % of all deaths among young people is accounted for by suicide. It is preventable, provided the risk factors and pre-suicidal behavior are identified for averting such a tragic happening. Pediatricians have crucial role to play in this.